The Effect of The Problem Based Learning Model With Animated Video on Students' Hots Ability on The Material On Human Movement Systems - Rohni Duani Purba; Jamalum Purba (Jurnal Pendidikan, Sains Sosial, dan Agama, 2025)
This study aims to investigate the effect of the Problem-Based Learning (PBL) model assisted by animated videos on students' Higher Order Thinking Skills (HOTS) in the topic of the human movement system among eighth-grade students at SMP Negeri 12 Medan. The research employed a pretest–posttest control group design with a sample of 60 students, divided into an experimental class (30 students using PBL with animated videos) and a control class (30 students using expository learning). Improvement in students' HOTS was measured using the N-Gain score from the average posttest results. The N-Gain score for the experimental class was categorized as moderate. The data were analyzed using a one-tailed t-test. The average posttest score of the experimental class was 84.50, compared to 67.50 in the control class. Hypothesis testing revealed tcount=2.32 and ttable=2.045, indicating that tcount > ttable. There- fore, it can be concluded that students taught with the Problem-Based Learning model assisted by animated videos achieved significantly higher HOTS compared to those taught with expository learning.